STRATEGI PENGEMBANGAN PARIWISATA CANDI GEDONGSONGO KABUPATEN SEMARANG - Sigalingging, Tessalonika Widi; Nurcahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
Gedongsongo Temple is a tourism destination located in Candi Village, Bandungan District, Central Java, Indonesia. The tourism potential involves temple buildings and cultural sustainability which is still very strong. However, during its development, Gedongsongo Temple faced several obstacles, such as limited bathroom facilities, the condition of the path to the temple which was damaged with lots of rocks, steep and uneven roads, as well as limited parking space and management which still needed to be improved. So, this research aims to analyze the potential and attractiveness of the Gedongsongo Temple tourist attraction, as well as formulate strategies for developing this tourist attraction. The research method used is mix methods, with data collection through observation, interviews, questionnaires and literature studies. This research uses strategic planning theory by John M. Bryson, along with SWOT analysis techniques, Internal Factor Analysis Summary (IFAS), and External Factor Analysis Summary (EFAS) used to analyze the data. The results of this research state that the recommended development strategy for Gedongsongo Temple managers is to utilize strengths and opportunities, which are reflected in Quadrant I, supporting the Growth Strategy. This indicates that the management of the Gedongsongo Temple tourist attraction can combine opportunities such as the popularity of the Gedongsongo Temple tourist destination in Semarang Regency, the government's high attention to the development of this tourism, the use of information technology as a promotional medium, contribution to job creation, and increasing the income of the surrounding community. . Apart from that, Gedongsongo Temple has historical value, such as the tradition of temple rehearsals or temple ruatan, especially in Semarang Regency. The suggestions from this research are to increase government attention, especially in developing tourist facilities and infrastructure at Gedongsongo Temple, preparing the temple rehearsal tradition or temple ruatan as a tourist event, and improving the quality of information technology as a medium, especially in providing information on entrance fees for Gedongsongo Temple tourism.